Mild NaCl Stress Influences Staphylococcal Enterotoxin C Transcription in a Time-Dependent Manner and Reduces Protein Expression - Etter, Danai; Ukowitz, Christina; Eicher, Corinne; Tasara, Taurai; Johler, Sophia (Frontiers in Microbiology, 2022)
Enterotoxins (SEs) produced by Staphylococcus (S.) aureus are the cause of serious food intoxications. Staphylococcal enterotoxin C (SEC) is one of the main contributors, as it is often highly expressed. S. aureus possesses a competitive growth advantage over accompanying bacterial flora under stress conditions encountered in foods, such as high NaCl concentrations. However, the influence of NaCl as an external stressor on SEC expression is still unclear. We investigated the influence of 4.5% NaCl on sec mRNA and SEC protein levels. A qRT-PCR assay revealed that NaCl stress leads to time dependently decreased or elevated sec mRNA levels for most strains. SEC protein levels were generally decreased under NaCl stress. Our findings suggest that NaCl stress lowers overall SEC concentration and time dependently affects sec mRNA levels.